Enhancement of sensing characteristics of Polydimethylsiloxane_based capacitive force sensor by introducing conductive polymer to dielectric layer - Yasumin Siangkhio; Adirek Rangkasikorn; Narin Tammarugwattana; Navaphun Kayunkid; Sukittaya Jessadaluk; Sakon Rahong; Supamas Wirunchit; Jiti Nukeaw (My University, 2020)
Abstract A capacitive force sensor is one of the electronics components used in several electronic devices and applications. An improvement of sensing characteristics of the sensor, for example sensitivity and response time, becomes an interesting research topic. The alternative approach to enhance the sensitivity and response time of polydimethylsiloxane‐based capacitive force sensors is proposed by introducing poly(3,4‐ethylenedioxythiophene) polystyrene sulphonate, a conductive polymer, into polydimethylsiloxane active layer. Two sensors using different active layers, (i) polydimethylsiloxane (conventional sensor) and (ii) poly(3,4‐ethylenedioxythiophene) polystyrene sulphonate mixed polydimethylsiloxane (modified sensor), were fabricated and characterised to reveal the sensing enhancement. Interestingly, the modified sensor shows the significant increase in the sensitivity from 0.7 to 1.14 kPa –1 (+62.86%) and the shortening response time from 1.55 to 0.43 s (−72.26%) with respect to the conventional sensor. In addition, the deterioration in elastic behaviour and the faster charge–discharge behaviour observed from the poly(3,4‐ethylenedioxythiophene) polystyrene sulphonate mixed polydimethylsiloxane film indicate the better deformation and charge transport than that from polydimethylsiloxane film. Therefore, it can be concluded that the conductive poly(3,4‐ethylenedioxythiophene) polystyrene sulfonate additive plays the role of mechanical and electrical modification of the polydimethylsiloxane active layer leading to the enhancement in sensitivity and response time of the polydimethylsiloxane‐based capacitive force sensor.
Keywords: Polydimethylsiloxane; Advanced Sensor and Energy Harvesting Materials